Coastal Community Perception Towards Disaster Mitigation and The Role of Mangrove Ecosystem in Pekon Way Jambu, Pesisir Barat, Lampung - Anisatu Z. Wakhidah; Suhendi (Al Jahiz, 2025)
Coastal communities in Pekon Way Jambu, Pesisir Barat, Lampung, are exposed to tsunami and coastal erosion risks, yet residential development continues in hazardous zones, thereby raising concerns about public awareness and preparedness. This study investigates the perceptions of coastal communities in Pekon Way Jambu, Pesisir Barat, Lampung, regarding disaster mitigation and the ecological and economic functions of mangrove ecosystems. Using a quantitative approach, data were gathered from 75 purposively selected respondents through a validated Likert-scale questionnaire assessing perceptions of coastal settlement, disaster preparedness, mangrove knowledge, and awareness of mangrove benefits. Findings reveal that while the community recognizes it inhabits a coastal area, understanding of tsunami mechanisms and spatial risks is limited. Preparedness is also poor, with little evidence of emergency kits, warning systems, or evacuation routes. However, respondents show moderate to good knowledge of mangroves, particularly their ecological role in wave attenuation and coastal protection. In contrast, awareness of their economic potential—such as for fisheries and ecotourism—remains low. The study highlights the importance of environmental education and community-based initiatives to enhance disaster awareness and ecosystem conservation. Strengthening theoretical and practical knowledge of sustainable mangrove use could serve dual purposes: increasing both community resilience and livelihood opportunities. These findings contribute to the design of ecosystem-based disaster mitigation models relevant to areas like Way Jambu, offering a foundation for collaboration among policymakers, educators, and conservation practitioners working on integrated coastal sustainability.